"Their Page is Still Up": Social Media and Coping with Loss. Issue 5 (4th July 2021) - Hoffman, Beth L.; Shensa, Ariel; Escobar-Viera, César G.; Sidani, Jaime E.; Miller, Elizabeth; Primack, Brian A.
Abstract: Young adults use social media (SM) to share life events, including loss of loved ones. In a national sample of U.S. young adults ( n  = 1, 119), "grievers" were identified as those who had experienced the loss of a loved one who had a SM account ( n  = 415, 37%). Logistic regression analyses found that grievers and non-grievers did not differ by sociodemographic status. Content analysis of open-ended items revealed four ways in which SM had a positive influence and five ways in which it had a negative influence on grievers. This study could inform the development of strategies to optimize SM use among grievers.